Private Lives in Public Places - Willcocks, Dianne (Taylor & Francis, 1987)
Public Order and Private Lives is a radical examination of the political forces which shape the law and order debate in Britain. Mike Brake and Chris Hale provide a hard-hitting analysis of Conservative policies on Crime, showing that, ironically, Conservative policies have created the very social conditions in which crime has flourished. They argue that the government is undermining basic civil liberties by its increased use of legislation as a means of control and coercion.